Conjugation of superparamagnetic iron oxide nanoparticles and curcumin photosensitizer to assist in photodynamic therapy - de Santana, Willian Max O.S. [UNESP]; Caetano, Bruno L. [UNESP]; de Annunzio, Sarah Raquel [UNESP]; Pulcinelli, Sandra H. [UNESP]; Ménager, Christine; Fontana, Carla Raquel [UNESP]; Santilli, Celso V. [UNESP] (Elsevier, 2020)
In this work, we describe the synthesis and characterization of the SPIONP-CUR conjugate between curcumin (CUR) and superparamagnetic iron oxide nanoparticles (SPIONPs), in addition to its application in photodynamic therapy (PDT) using a protocol free of organic solvents as a dispersant. The SPIONP-CUR conjugate was characterized by X-ray diffraction, transmission electron microscopy, zeta potential measurements, Fourier transform infrared spectroscopy, thermogravimetry, magnetometry and magnetic hyperthermia assays. The SPIONP-CUR conjugation occurred by bonding between the keto-enol moiety of CUR and the iron atoms present on the surfaces of the SPIONPs. The conjugate showed heating power under an alternating magnetic field (AMF) and photodynamic action when irradiated with blue LED light. In experiments using PDT against Staphylococcus aureus in the planktonic phase, it was demonstrated that with application of blue light at 3.12 J cm−2, the conjugate (dispersed in water) caused a total reduction of the bacterial load. In the absence of light, the reduction was insignificant, even after 24 h of contact with the bacteria.
Keywords: Antimicrobial; Curcumin; Magnetic nanoparticles; Photodynamic therapy; Staphylococcus aureus